T‐Cell‐Mimicking Nanoparticles for Cancer Immunotherapy. Issue 39 (18th August 2020) - Kang, Mikyung; Hong, Jihye; Jung, Mungyo; Kwon, Sung Pil; Song, Seuk Young; Kim, Han Young; Lee, Ju‐Ro; Kang, Seokyung; Han, Jin; Koo, Ja‐Hyun; Ryu, Ju Hee; Lim, Songhyun; et al.
Abstract: Cancer immunotherapies, including adoptive T cell transfer and immune checkpoint blockades, have recently shown considerable success in cancer treatment. Nevertheless, transferred T cells often become exhausted because of the immunosuppressive tumor microenvironment. Immune checkpoint blockades, in contrast, can reinvigorate the exhausted T cells; however, the therapeutic efficacy is modest in 70–80% of patients. To address some of the challenges faced by the current cancer treatments, here T‐cell‐membrane‐coated nanoparticles (TCMNPs) are developed for cancer immunotherapy. Similar to cytotoxic T cells, TCMNPs can be targeted at tumors via T‐cell‐membrane‐originated proteins and kill cancer cells by releasing anticancer molecules and inducing Fas‐ligand‐mediated apoptosis. Unlike cytotoxic T cells, TCMNPs are resistant to immunosuppressive molecules (e.g., transforming growth factor‐β1 (TGF‐β1)) and programmed death‐ligand 1 (PD‐L1) of cancer cells by scavenging TGF‐β1 and PD‐L1. Indeed, TCMNPs exhibit higher therapeutic efficacy than an immune checkpoint blockade in melanoma treatment. Furthermore, the anti‐tumoral actions of TCMNPs are also demonstrated in the treatment of lung cancer in an antigen‐nonspecific manner. Taken together, TCMNPs have a potential to improve the current cancer immunotherapy. Abstract : T‐cell‐membrane‐coated nanoparticles (TCMNPs) are developed for cancer immunotherapy. The TCMNPs can be targeted at tumors and kill cancer cells while being resistant to the pro‐tumoral factors in the tumor microenvironment. Indeed, the TCMNPs exhibit a higher therapeutic efficacy than current cancer treatments based on immune checkpoint blockade, and they are effective for the treatment of various tumors.